DINÁMICA LIMNOLÓGICA DE LA LAGUNA SAUSACOCHA DE ALTA MONTAÑA, HUAMACHUCO, AGOSTO A DICIEMBRE 2018 - ESPARZA TACANGA, Solange Arlette (2019)
The investigation was carried out in the Sausacocha Lagoon located in Huamachuco-La Libertad at 7 ° 47´45.28” south latitude and 77 ° 59´27.20” west longitude, at an altitude of 3200 meters above sea level. Two sampling stations were established: shore and center. 6 samples were taken from August to December 2018. The objective of the study is to describe the dynamics of the Sausacocha high mountain lagoon through the behavior of meteorological, physical, chemical and biological characteristics, in such a way that awareness and responsibility are generated environmental management of this ecosystem-aquatic. The physical and chemical parameters were performed in situ and a HACH multiparameter model HQ40d was used. For macroinvertebrates a Surber network of 300 μm and the plankton a standard network of 20 um. Chlorophyll- "a" with the spectrophotometer. Water temperature values varied from 15.4 to 19.5 ° C, of dissolved oxygen 5.2 to 6.8 mg / L, pH 6.7 to 8.4. and an electrical conductivity of 31.3 to 34.5 μS / cm. 11 species of phytoplankton were identified, predominance of diatoms. In the MIAs, 9 families were identified, with the Chironomidae family prevailing. The values of physical and chemical parameters were found within the ECA (2017) - Category 4 and are suitable for the subsistence of biological species. At a biological level, it had a moderately contaminated and regular quality water assessment.